Shari'ah Compliant Matrix for Humanizing Productivity - Category 7: Socialization and Community Engagement - Jamaludin, Mohammad Aizat; Kartika, Betania; Mahamad Maifiah, Mohd Hafidz; Tukiran, Nur Azira; Ghalia, Bouhedda (2021)
This training slide is part of the Shari'ah-compliant appraisal matrix that focuses on Socialization and Community Engagement (SCE) elements. As a core element of higher learning institutions, Socialization and Community Engagement (SCE) adopts a more systematic and holistic approach in the provision of humanising education.